2021
DOI: 10.3390/ijerph18178927
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance and Optimal Cut-Off Points of Blood Pressure for Identifying Arteriosclerosis among Adults in Eastern China

Abstract: This study aimed to assess the predictive performance and establish optimal cut-off points of blood pressure for identifying arteriosclerosis in eastern Chinese adults. Brachial–ankle pulse wave velocity (baPWV) was utilized to evaluate arteriosclerosis. The predictive performance of blood pressure for arteriosclerosis was determined by the area under the curve (AUC) of receiver operating characteristics; the optimal blood pressure cut-off points were determined by Youden’s index. A logistic regression model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…CVD and obesity are two major threats to public health (He et al, 2022). Arteriosclerosis is the dominant cause of CVD (Gavornik & Galbavy, 2001; Yu et al, 2021). In this study, the results of the two-way ANOVA and the unconditional logistic regression models showed that hypertension was statistically significant in both baPWV and arteriosclerosis, which may suggest that hypertension is a crucial factor influencing arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CVD and obesity are two major threats to public health (He et al, 2022). Arteriosclerosis is the dominant cause of CVD (Gavornik & Galbavy, 2001; Yu et al, 2021). In this study, the results of the two-way ANOVA and the unconditional logistic regression models showed that hypertension was statistically significant in both baPWV and arteriosclerosis, which may suggest that hypertension is a crucial factor influencing arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both sides are measured and the abnormal side is taken for the analysis. Arteriosclerosis was defined as a baPWV ≥ 1400 cm/s (Yu et al, 2021). The ABI was calculated by dividing the SBP at the ankle by the SBP in the arm (Al-Qaisi et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations